Hydrogen production by water electrolysis technologies: A review - El-Shafie, Mostafa (Results in engineering, 2023)
Hydrogen as an energy source has been identified as an optimal pathway for mitigating climate change by combining renewable electricity with water electrolysis systems. Proton exchange membrane (PEM) technology has received a substantial amount of attention because of its ability to efficiently produce high-purity hydrogen while minimising challenges associated with handling and maintenance. Another hydrogen generation technology, alkaline water electrolysis (AWE), has been widely used in commercial hydrogen production applications. Anion exchange membrane (AEM) technology can produce hydrogen at relatively low costs because the noble metal catalysts used in PEM and AWE systems are replaced with conventional low-cost electrocatalysts. Solid oxide electrolyzer cell (SOEC) technology is another electrolysis technology for producing hydrogen at relatively high conversion efficiencies, low cost, and with low associated emissions. However, the operating temperatures of SOECs are high which necessitates long startup times. This review addresses the current state of technologies capable of using impure water in water electrolysis systems. Commercially available water electrolysis systems were extensively discussed and compared. The technical barriers of hydrogen production by PEM and AEM were also investigated. Furthermore, commercial PEM stack electrolyzer performance was evaluated using artificial river water (soft water). An integrated system approach was recommended for meeting the power and pure water demands using reversible seawater by combining renewable electricity, water electrolysis, and fuel cells. AEM performance was considered to be low, requiring further developments to enhance the membrane's lifetime.